Design and analysis of plastic gears in rack and pinion steering system for formula supra car. (2018) - Chopane, Ashwin; Gupta, Shanu; Ajit, Abhiram; Kakroo, Sushant; Salve, Aniket
Abstract: Plastic gears have positioned themselves as serious alternatives to traditional metal gears in a wide variety of applications. The use of plastic gears has expanded from low power, precision motion transmission into more demanding power transmission applications. In an automobile, the steering system is one of the most important systems which used to control the direction and stability of a vehicle. In order to have an efficient steering system, one should consider the material and properties of gears used in rack and pinion. Using plastic gears in a vehicle's steering system has many advantages over the current traditional use of metallic gears. High performance plastics like, glass fiber reinforced nylon 66 have less weight, resistance to corrosion, noiseless running, lower coefficient of friction and ability to run without external lubrication. Moreover, plastic gears can be cut like their metal counterparts and machined for high precision with close tolerances. In formula supra vehicles, weight, simplicity and accuracy of systems have prime importance. These requirements make plastic gearing the ideal option in its systems. An effort is made in this paper for analyzing the possibility to rebuild the steering system of a formula supra car using plastic gears keeping contact stresses and bending stresses in considerations. As a conclusion the use of high strength engineering plastics in the steering system of a formula supra vehicle will make the system lighter and more efficient than traditionally used metallic gears.